Fuel production with heterogeneous catalysis - Sá, Jacinto; Bal, Rajaram (CRC Press/Taylor & Francis Group, 2015)
Fuel Production with Heterogeneous Catalysis presents the groundbreaking discoveries, recent developments, and future perspectives of one of the most important areas of renewable energy research-the heterogeneous catalytic production of fuels. Comprised of chapters authored by leading experts in the field, this authoritative text: focuses primarily on the state-of-the-art catalysts and catalytic processes anticipated to play a pivotal role in the production of fuels; describes production of fuels from renewable sources using environmentally friendly technologies; exposes the advantages and disadvantages of each production process; suggests solutions to minimize the impact of fuel transportation; conveys the importance of catalysis for the sustainable production of fuels.
Keywords: Fuel.; Heterogeneous catalysis.; elektronické knihy; electronic books